Rehabilitation outcomes of stroke patients with low left ventricular ejection fraction in the subacute rehabilitation phase - Masahiro Tsujikawa; Yohei Otaka; Rei Hasegawa; Kunitsugu Kondo; Kaori Muraoka; Meigen Liu (Medical Journals Sweden, 2018)
Objective: To examine the left ventricular ejection fraction in patients with subacute stroke and compare rehabilitation outcomes between those with decreased left ventricular ejection fraction and those without. Design: Retrospective chart review. Subjects: A total of 482 consecutive patients with stroke admitted to a convalescent rehabilitation hospital. Methods: Patients were assessed using transthoracic echocardiography within 7 days of admission. The patients were divided into a group with low left ventricular ejection fraction and a group with preserved left ventricular ejection fraction. Functional Independence Measure (FIM) scores at admission and discharge, FIM gain, FIM efficiency, and discharge disposition were compared between groups. Results: The low left ventricular ejection fraction group had significantly lower cognitive and total FIM scores on admission than the preserved left ventricular ejection fraction group. The patients in the low left ventricular ejection fraction group tended to be transferred to acute hospitals more frequently. How-ever, the total score of discharge FIM, FIM gain, and FIM efficiency did not differ significantly between the groups when rehabilitation was continued until discharge. Conclusion: Stroke patients with low left ventricular ejection fraction in the subacute phase could achieve almost the same functional outcomes as those of patients with preserved left ventricular ejection fraction. Although the general medical condition should be considered, the finding of low left ventricular ejection fraction did not pose a barrier to successful rehabilitation after stroke.